2021
DOI: 10.3390/f12081082
|View full text |Cite
|
Sign up to set email alerts
|

InVEST Model-Based Spatiotemporal Analysis of Water Supply Services in the Zhangcheng District

Abstract: The Zhangcheng District is critically responsible for protecting water resources, preserving sand sources, and improving the ecological environment in Beijing. Quantitative evaluation and research on the ecosystem water supply services in this area are beneficial for developing conservation planning and establishing ecological compensation mechanisms in water conservation areas. In this paper, based on the land use, meteorological, soil, and field observation data of the research area, the InVEST water yield m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Therefore, the PLUS model is chosen to accurately simulate the spatial distribution by predicting land changes with future factor constraints. With the current in-depth research on ESs, numerous models can quantify them, such as InVEST [15], ARIES [16], ESM [17], and EcoMetrix [18], among which the InVEST model is more mature and can be used for largescale quantitative studies, the model has lower data requirements, lower computational workload, and higher accuracy of conclusions, and is widely used [19][20][21], while studies in the Chinese region have also shown strong applicability to evaluate and analyze a variety of indicators in time space and detect dynamic distribution changes [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the PLUS model is chosen to accurately simulate the spatial distribution by predicting land changes with future factor constraints. With the current in-depth research on ESs, numerous models can quantify them, such as InVEST [15], ARIES [16], ESM [17], and EcoMetrix [18], among which the InVEST model is more mature and can be used for largescale quantitative studies, the model has lower data requirements, lower computational workload, and higher accuracy of conclusions, and is widely used [19][20][21], while studies in the Chinese region have also shown strong applicability to evaluate and analyze a variety of indicators in time space and detect dynamic distribution changes [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Water yield refers to the runoff volume reaching the catchment area after precipitation flows over the ground. Its variation reflects the water retention capacity of vegetation or soil [3][4][5]. A high water yield per unit area indicates a lower retention capacity of vegetation or soil, whereas a lower water yield suggests a higher retention capacity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Benra et al [22] used the InVEST seasonal water yield model to assess the water monitoring performance of 224 catchments in southern Chile, helping inform water supply policy decisions. Liu et al [23] utilized the InVEST annual water yield model to estimate the water supply of the Beijing Zhangcheng district ecosystem and quantitatively analyzed the characteristics of the spatiotemporal distribution of WSSs in the watershed and the influence of different topographic factors, which is conducive to formulating water conservation region protection and establishing ecological compensation mechanisms. Bejagam et al [24] used the InVEST annual water yield model to analyze the impacts of climate change on water supply and water-associated services such as hydropower generation in the densely populated Tungabhadra Basin.…”
Section: Introductionmentioning
confidence: 99%